2021
DOI: 10.1080/20550324.2021.1936972
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of reinforcement properties of nano-CaCO3 synthesized from Achatina fulica snail shell through mechanochemical methods on epoxy nanocomposites

Abstract: The current study investigates the reinforcement properties of novel nano-calcium carbonate (nano-CaCO 3 ) synthesized from Achatina fulica snail shell. The shell was wet-milled to nanoparticle sizes using mechanochemical procedures. Epoxy nanocomposites prepared with nanofiller content ranges of 1-7 wt.% were fabricated using a conventional resin casting method. Thermal stability and degradation with mechanical properties such as tensile strength, impact strength, and the hardness properties of prepared nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
4
14
0
Order By: Relevance
“…This output may be attributed to the reinforcement effect of the nanoparticle incorporated. It also confirmed the positive reinforcement effects of the snail shell nano-CaCO 3 , montmorillonite, and kaolinite as reported in the available literature [ 26 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This output may be attributed to the reinforcement effect of the nanoparticle incorporated. It also confirmed the positive reinforcement effects of the snail shell nano-CaCO 3 , montmorillonite, and kaolinite as reported in the available literature [ 26 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultssupporting
confidence: 87%
“…It was observed that the addition of 1 wt.% snail shell nanoparticles ( SS1 ) enhanced the strength of greenpoxy by 62%, which was higher than the 8 % and 13 % tensile strength improvement observed after loading the same percentage of montmorillonite and kaolinite, respectively. This output proves the effectiveness of snail shell nanoparticles on the strength of greenpoxy at low loadings [ 13 , 37 ]. The homogeneous dispersion of nanoparticles in the matrix, forming an interlocking structure, may also account for the improved tensile strength observed at a low loading of the snail shell nanoparticles [ 14 ].…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…25 This significant improvement in mechanical properties may be attributed to the reinforcing effect of nanoparticles incorporated at low concentrations. 26,27 A sharp drop in tensile strength at the loading of CNC above 2.5 wt.% may be attributed to aggregation of the nanoparticles and the loading effect of the other components, producing a weaker structure and resulting in reduced tensile strength and Young's modulus.…”
Section: The Interaction Effect Of Pva and Cnc On Bioplastic Mechanic...mentioning
confidence: 99%
“…The use of SSN has been reported in previous studies to have a strong reinforcement influence on mechanical properties. 27,28 Uniform dispersion of the nanoparticles in the matrix of the films (Figure 3) provided for a more robust structure with high resistance to pulling stress, resulting in increased mechanical properties.…”
Section: The Interaction Effect Of Ssn and Pva On Bioplastic Mechanic...mentioning
confidence: 99%